SYSTEM-LOGICAL APPROACH TO THE ORGANIZATION OF DISTANCE LEARNING IN THE MILITARY EDUCATION SYSTEM - Gorodianska, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article substantiates the principles and foundations of the system-logical approach to the organization of the educational process using distance learning in a military educational institution. The need for defense reform is due to the fact that against the background of many dynamic changes in modern society, which are characterized by uncertainty and instability along with hybrid warfare, digitalization of society, many problems arise in certain sectors of life and security, and, first of all, in such an important sector. as education in general and military education in particular. That is why the task is to update the military education system in order to prevent the consequences of possible negative events and develop appropriate countermeasures. One of the measures to preserve the stable functioning of the military education system is the introduction and further development of distance learning. This requires specific approaches to the organization of the educational process. The role, place and principles of the system-logical approach to the organization of the educational process by distance learning in a military educational institution have been substantiated. It is shown that the essence of a systematic approach to the problem of the formation of a distance learning system lies in the understanding of the educational process and the management system of educational and educational activities as components of an integral complex system of military education. At the same time, as subsystems, linked by a common goal and objectives of training and education, taking into account their role and place among other systems. A logical approach to the analysis of complex systems should form the basis of a systemlogical approach to the formation of the educational process in military educational institutions. The tasks of the logical approach are to recreate the essence or the main content of the research subject and present it in the form of mental abstractions. In this case, the logical method is based on the laws and requirements (categories) of formal and dialectical logic. It has been substantiated that a rational, truly scientific system of organizing the educational process for distance learning in a military educational institution should be based on a systematic and logical approach, ensure a high level of professional competencies of military specialists of the corresponding educational level and resist possible external and internal threats.